2019
DOI: 10.21608/ejchem.2019.10157.1687
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Properties of Wool fibers pretreated with chitosan and nano chitosan and dyed with saffron natural dye.

Abstract: W OOL fibers pretreated with chitosan and nano-chitosan and dyed with saffron red and yellow mixture as natural dye by using microwave heating method. The effect of chitosan and nano chitosan concentrations on color strength (K/S) was measured. The results indicated that, wool fibers pretreated with chitosan and nano chitosan recorded higher color strength than the untreated fibers. Fastness properties and the color yield of the dye on wool fibers were evaluated. The results indicated that color fastness to ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…From Table 4, it is clear that treating with chitosan generally could decrease the values of L* meaning that the color of the treated fabrics got darker than the untreated fabrics. The same observation was also obtained by Ali, El-Khatib, & EL-Mohamedy (2019).…”
Section: Color Parameterssupporting
confidence: 85%
See 1 more Smart Citation
“…From Table 4, it is clear that treating with chitosan generally could decrease the values of L* meaning that the color of the treated fabrics got darker than the untreated fabrics. The same observation was also obtained by Ali, El-Khatib, & EL-Mohamedy (2019).…”
Section: Color Parameterssupporting
confidence: 85%
“…This finding is also consistent with the other findings. Ali, El-Khatib, & EL-Mohamedy (2019) showed that the color strength of pretreated wool fibers with nanochitosan and chitosan and dyed with saffron red and yellow mixture has high value of color strength than untreated wool fibers. The same observation was also found by Yadav, Singh, Kaur, & Sahu (2019).…”
Section: K/s Valuementioning
confidence: 98%
“…[3,12,46,69,70] It is known to be the costliest plant grown anywhere in the world. [46,71,72] Saffron flowers are light purple with reddish and yellowish thread derived from the plant's dried stigmas and are described as a flavour with a distinctive natural colourant and have also been utilized in the cosmetics industry [12,71,73,74] The image of the saffron plant was showed in Fig. 16.…”
Section: The Dye Extracted From Psidium Guajava Leaves Using the Aque...mentioning
confidence: 99%
“…Environmentally friendly treatments such as biopolymers are used instead of chemical treatments to remove chemical pollutants and their residues resulting from chemical processes [15]. The natural polysaccharide was applied to treat natural fibers [cotton, wool, silk] to improve their properties because natural textiles especially those made from cellulose fibers and protein fibers are potential candidates for the growth and transmission of pathogenic organisms due to their porous structure and ability to retain moisture, they provide suitable conditions for microbes [16].…”
Section: Introductionmentioning
confidence: 99%